Statistical Analysis of Maternal Health Disparities Among Working Women and Housewives: A Cross-Sectional Study on Pregnancy-Related Issues, Safe Childbirth, and Maternal Mortality. - Atif, Muhammad; Ayub, Gohar; Afridi, Irum; Farooq, Muhammad; Shafiq, Muhammad; Ilyas, Muhammad; Rasikh, Zia Ur Rahman (Inquiry (00469580), 2026)
Maternal health remains a critical public health concern, particularly in developing countries where disparities persist across different socioeconomic and occupational groups. Working women and housewives often face different levels of access to healthcare, stress, and awareness, all of which can influence pregnancy outcomes. Understanding these factors is essential for developing targeted interventions and policies that improve maternal health outcomes for all women. This study analyzes data from Pakistan Maternal Mortality Survey 2019, which employed a multistage, multiphase cluster sampling to ensure nationally representative estimates of maternal health indicators. In this study, chi-square test, multinomial regression, and clustering techniques were utilized to identify the leading causes of maternal mortality. The results of this study reveal significant differences in maternal health outcomes between working women and housewives in Pakistan. Among the 1177 maternal deaths, 532 (45.20%) were working women, while 645 (54.80%) were housewives. Working women experienced higher rates of seizures (47.62%), chest pain (46.81%), and stress-related conditions, while housewives frequently reported weight loss (52.38%), general abdominal pain, and health issues associated with household environments, such as exposure to polluted water. The principal determinants of maternal death among working women included unhealthy lifestyles, job-related anxiety, and frequent travel. In contrast, maternal health complications among housewives were largely attributed to asthma, carelessness during domestic chores, and lack of exercise. The study highlights the importance of targeted interventions, including better workplace policies for working women and awareness programs for housewives.